Analisis Perbandingan Return Investasi Emas dan Saham Studi Kasus PT. Aneka Tambang Tbk - neni triana; gazali Syamni (JAKTABANGUN: Jurnal Akuntansi dan Pembangunan, 2021)
This study examined the comparison of returns between gold and stock investments at PT Aneka Tambang Tbk during 2015-2020. This study used secondary data and information collected through historical data, namely the price of gold and the stock prices of PT Aneka Tambang Tbk. The movement of gold and stock prices was observed every day for six years and then averaged every month. The data analysis used was t-tests (Independent Sample t-test) with a significance of five percent. The results showed that during the six years, there was no comparison between gold returns and stocks of PT Aneka Tambang. While the results of the annual study analysis found that in 2015 and 2016, there was a differences of returns between gold and stocks. In 2018, 2019, and 2020 there was no comparison of returns between gold and stocks of PT Aneka Tambang Tbk.